G30 Paediatric Jejunal feeding is resource intensive; report of 5 year practice in Wessex. (27th April 2016) - Everitt, L; Dick, K; Pridgeon, J; Tighe, MP; Ward, N; Portess, H; Stanton, MP; Afzal, NA
Abstract : Aims: Use of paediatric jejunal feeding (JF) is increasing. There is limited information on its long-term use with a notable absence of national guidance on JF in children. We present an audit of paediatric jejunal feeding practice in the Wessex Region over the last 5 years. Methods: Paediatric patients initiating JF for longer than three months, across the 12 centres in Wessex, were included in the study. The total review period was last 5 years. Patients were identified from a paediatric surgical database with analysis of data including demographics, underlying diagnosis, placement indication, previous enteral feeding intervention, insertion technique, tube type and complications including tube survival and replacement frequency. Results: 50 children (54% male, median age 1.68 yrs – IQR 0.74–7.46 yrs) initiated JF during the study period; 60% of children < 2 years of age. 48% had a syndrome and 62% a neurological diagnosis. Severe gastroesophageal reflux with inability to tolerate gastric feeding was the primary indication for JF in 84% of children with a median weight of –1.86 SDS (IQR −3.7 – −0.81) with 78% receiving feeds via gastrostomy immediately prior to JT insertion. 18/50 of children initiated JF via nasal and 32/50 via gastrojejunal route (26/50 via Balloon-button G-J tube and 6/50 Freka PEG- J tube). The median follow up period was 2.9 years (IQR 1.6–6.4 yrs) during which 35 elective and 103 emergency replacements were needed; tip dislodgement being the commonest reason. The jejunal tube was successfully removed in 17 (median use 1.3 yrs – IQR 0.5–3.3), with 10% exclusively oral fed at last follow up. Conclusion: We report a large cohort of jejunally fed children in the Wessex with more than 60% dependent on jejunal feeding at 5 years follow up. Paediatric JF is resource intensive requiring radiologic, surgical, gastrointestinal and dietetic services for insertion, feed management and replacement of jejunal tubes when required. We raise the need for national guidelines for indications of J tube placement, monitoring and management.